015 Predicting a diagnosis of pathologically confirmed vasculitic neuropathy. Issue 6 (24th May 2018) - Nathani, Dev; Barnett, Michael H; Spies, Judith; Pollard, John; Kiernan, Matthew C
Abstract : Introduction: Nerve biopsy remains the gold standard to diagnose vasculitic neuropathy. Conversely, biopsy has imperfect sensitivity and entails risks associated with an invasive procedure. Methods to improve diagnostic accuracy remain important considerations given the severity of the disease, added with the risks associated with subsequent therapy, particularly in ill-defined cases. Methods: Clinical, laboratory and neurophysiological parameters were analysed for all patients who subsequently underwent biopsy. Nerve and muscle biopsy reports were assigned pathologic categories of definite, probable, possible or absent vasculitis using standard guidelines. Correlations were assessed between pre-biopsy parameters and subsequent diagnosis of definite or probable vasculitic neuropathy (pathologically confirmed vasculitis). Results: From a cohort of 207 patients who underwent nerve biopsy over 21 months, 70 were suspected of having vasculitic neuropathy prior to biopsy. Of the 70 patients, vasculitis was confirmed as definite (11.4%), probable (15.7%) or possible (10.0%) on neuropathological assessment. The most sensitive parameters for pathologically confirmed vasculitis were the presence of sensorimotor neuropathy (78%) and axonal neuropathy (67%) on nerve conduction studies (NCS) in the overall cohort. Pathologically absent vasculitis was most prevalent in patients with normal NCS (90%), chronic, symmetric symptoms (86%) and demyelinating findings on NCS (79%). The parameters with the strongest associations with pathologically confirmed vasculitis were positive autoantibody serology (50.0% vs 21.1%, p<0.01), anti-neutrophil cytoplasmic antibody (27.3% vs 6.4%, p<0.01), anti-myeloperoxidase antibody (22.7% vs 1.8%, p<0.005) and rheumatoid factor (22.7% vs 2.8%, p<0.005). In patients suspected to have vasculitis, 83.3% of anti-myeloperoxidase antibody positive patients had pathologically confirmed vasculitis. In patients not suspected to have vasculitis, acute symptoms had the strongest association with pathologically confirmed vasculitis (36.4% vs 10.5%, p<0.05). Conclusion: Specific characteristics of symptoms at the time of presentation, combined with the presence of autoantibodies and neurophysiological abnormalities, were predictive of a tissue diagnosis of vasculitic neuropathy.